1984
DOI: 10.1029/jc089ic06p10529
|View full text |Cite
|
Sign up to set email alerts
|

A theory of the imaging mechanism of underwater bottom topography by real and synthetic aperture radar

Abstract: A simple theoretical model of the imaging mechanism of underwater bottom topography in tidal channels by real and by synthetic aperture radar (SAR) is presented. The imaging is attributed to surface effects induced by current variations over bottom topography. The current modulates the short‐scale surface roughness, which in turn gives rise to changes in radar reflectivity. The bottom topography‐current interaction is described by the continuity equation, and the current‐short surface wave interaction is descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
189
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 336 publications
(210 citation statements)
references
References 28 publications
6
189
0
4
Order By: Relevance
“…[9] Weak hydrodynamic interaction theory has been used to describe the interaction of the surface short water waves with a variable current [Alpers and Hennings, 1984]. The first-order expression is deduced based on the Fourier transform as…”
Section: Mechanismmentioning
confidence: 99%
See 3 more Smart Citations
“…[9] Weak hydrodynamic interaction theory has been used to describe the interaction of the surface short water waves with a variable current [Alpers and Hennings, 1984]. The first-order expression is deduced based on the Fourier transform as…”
Section: Mechanismmentioning
confidence: 99%
“…According to Alpers and Hennings [1984], u(K) is expressed as [10] The term K(U 0 + c g ) in equation (1) is defined as the advection rate m a [Alpers and Hennings, 1984] and its reciprocal is the advection time t a…”
Section: Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Since then, numerous studies have found that under low-to-moderate wind and strong tidal current conditions, real aperture radar and synthetic aperture radar (SAR) can detect bottom topography features in both shallow 1,[5][6][7] and deep waters. 2 One-dimensional (1-D) SAR imaging of shallow water bottom topography was first proposed by Alpers and Hennings,8 and a theoretical model was provided. 8,9 Many researchers have subsequently studied ocean topography in SAR images worldwide.…”
Section: Introductionmentioning
confidence: 99%